Association of phosphatase and tension homologue deleted on chromosome ten polymorphism rs1903858, but not serum levels with the risk of non–small‐cell lung cancer: A case‐control study. Issue 8 (15th June 2020) - Liang, Zhen; Tang, Yuzhu; Li, Hao; Xie, Youjun; Zhan, Lingling
Abstract : Background: To investigate the association between phosphatase and tension homologue deleted on chromosome ten ( PTEN ) gene polymorphisms and non–small‐cell lung cancer (NSCLC) and further identify whether these polymorphisms influence serum PTEN levels. Methods: A total of 152 NSCLC patients and 124 healthy controls were included in the study. PTEN gene rs11202586 (T > C) and rs1903858 (A > G) polymorphisms were detected using the multiple single‐base extension technique (SNaPshot). The serum PTEN levels were determined using an enzyme‐linked immunosorbent assay (ELISA) kit. Results: The rs1903858 AG, GG genotypes, and G allele were associated with a higher risk of NSCLC (odds ratio (OR) =2.079, 95% confidence interval (CI) = 1.087‐3.974, P  = .027; OR = 1.897, 95%CI = 1.053‐3.419, P  = .033; OR = 1.505, 95%CI = 1.065‐2.126, P  = .020). Stratified analysis reveal that the rs1903858 GG genotype and G allele were associated with an increased risk of squamous cell carcinoma (SCC) (OR = 3.226, 95%CI = 1.075‐9.678, P  = .037; OR = 1.873, 95%CI = 1.092‐3.212, P  = .023). Among smokers, the rs1903858 G allele carriers have an increased risk of NSCLC (OR = 1.916, 95%CI = 1.023‐3.589, P  = .042), but a decreased risk of NSCLC was found with the AT haplotype. With respect to the serum PTEN levels, no significant difference was noted between NSCLC patients and healthy controls in this study. Conclusions: The study indicated that the rs1903858 gene polymorphism is associated with increased risk of NSCLC, particularly in SCC and smoker, and the haplotype AT was a protective factor for NSCLC. The serum PTEN levels were not associated with NSCLC.